Implementasi Sistem Informasi di UPT Laboratorium Kesehatan dan Lingkungan Dinas Kesehatan Provinsi Riau - Rahayu, Fitri; Zaman, M. Kamali; Misnaimah, Misnaimah (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to analyze the information system in the Environmental Health Laboratory Integrated Service Unit of the Riau Provincial Health Service. Data was collected through interviews, document searches and field observations. Data analysis was carried out by analyzing patterns of cause and effect relationships using the USG management method (Urgency, Seriousness and Growth) and data analysis using fishbone diagrams. The results of this research conclude that the implementation of the information system program at the Health and Environment Laboratory of the Riau Province Health Service requires 4 (four) aspects, namely sufficient human resources (HR), adequate funds, methods that suit conditions and needs, and equipment that is well maintained.